2021
DOI: 10.1177/17562864211006503
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiologic features and therapeutic strategies in tumefactive demyelination: a retrospective analysis of 50 consecutive cases

Abstract: Aims: Our goal was to expand the spectrum of clinico-radiologic characteristics and the possible therapeutic choices in patients with tumefactive demyelinating lesions (TDLs). Methods: A retrospective analysis of 50 patients with at least one TDL was performed at an academic neurology center (2008–2020). Results: Our cohort comprised mostly women (33/50) with a mean age of 38 years at TDL onset. The mean follow-up time was 76 months. The mean Expanded Disability Status Scale score at TDL onset and at the lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…They stated that there were no correlations between treatment and disease outcome. Vakrakou et al suggested that when corticosteroids and plasma exchange are ineffective, cyclophosphamide can be an additional treatment option for TD ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…They stated that there were no correlations between treatment and disease outcome. Vakrakou et al suggested that when corticosteroids and plasma exchange are ineffective, cyclophosphamide can be an additional treatment option for TD ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide has shown effectiveness in aggressive disease courses indicated by a poor response to corticosteroids and plasma exchange failure. Lessons from drug-related TDL, immunopathology studies of biopsied lesions and clinical cases reports indicate different cellular and humoral mechanisms implicated in the pathogenesis; lymphopenia-induced lymphoproliferation, persistent selected peripheral lymphopenia (CD8 or CD4 T cells), exaggerated innate immunity response either with pathogenic potential or regulatory / compensatory potential and exaggerated B cells response ( 16 , 99 ).…”
Section: Scientific Questions and Future Directionsmentioning
confidence: 99%
“…In our recent study, we analyzed the characteristics and outcomes of patients with recurrent TDLs ( 16 ). We also provided a therapeutic algorithm mainly based on the observed clinico-radiological response to treatment options at various time points.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide infusions were discontinued and a steroid pulse therapy was performed. The patient was switched to rituximab with a dosing schedule of 1 g at days 1 Letter to the Editor Therapeutic Advances in Neurological Disorders 14 later. After 24 months from disease onset, the patient had mild right hemiparesis (EDSS score 2) and showed no evidence of disease activity on brain MRI.…”
mentioning
confidence: 99%
“…We read with interest the recent article by Vakrakou et al 1 about a retrospective analysis of clinico-radiological characteristics of patients with tumefactive demyelinating lesions (TDLs) and the seven-group stratification proposal. For group A, consistent with Marburg-like TDL, the authors proposed cyclophosphamide as a valid therapeutic option and reopened the debate about the treatment of aggressive demyelinating disorders.…”
mentioning
confidence: 99%